Intestinal T-cell lymphoma with eosinophilic infiltration in a cat: a cytohistopathological evaluation with immunophenotyping (Veterinary Science Development, 2017)
In the present study, we describe the cytohistopathological and immunohistochemical characteristics of the intestinal Tcell lymphoma in a seven-year-old male Persian cat, applying the World Health Organization (WHO) system for the classification of domestic animal lymphomas. In fine-needle aspiration, mesenteric lymph nodes contained many lymphocytes from small- to medium-size, a few lymphoblasts and plasma cells, and rare eosinophils suggestive of hyperplastic lymph node. Histopathologically, diffuse infiltration and proliferation of tumor cells in the large intestine mucosa with architectural distortion of the crypts to the tunica muscularis in the submucosa and mucosal ulceration were observed. The tumor cells were composed of small-to-intermediate-sized lymphocytes with round, monomorphic nuclei and scantto- moderate cytoplasm. Eosinophils infiltration was present. The mitotic rate was low. Immunohistochemical analysis revealed that neoplastic cells were mostly and strongly positive for T-cell phenotype CD3+ but negative for B-cell phenotypes CD20- and CD79a-. On the basis of cytology, histopathology, and immunohistochemical findings, the present tumor was diagnosed as intestinal T-cell lymphoma, according to WHO histological classification. Applying the WHO classification system for the diagnosis of feline lymphomas is very useful and has high accuracy and consistency. Although cytological examination may assist in the evaluation of gastrointestinal disease, histopathological examination is necessary to establish a definitive diagnosis of alimentary lymphoma.